Tyrosinase Inhibitors Among Flora of Lubelskie Region—Application of Bio-Chromatographic Approach and Zebrafish Model in Bioactivity Screening of Plant Material - Kamila Kusio-Targońska; Nataliia Kosheva; Krzysztof Kamil Wojtanowski; Katarzyna Gaweł-Bęben; Dimitris Beis; Wirginia Kukula-Koch (Molecules)
The whitening potential of natural products is commonly assessed through spectrophotometric assays that colorimetrically measure the inhibitory effects on tyrosinase, a key enzyme in pigment formation. However, these assays fail to provide evidence about the input of individual components into the total activity of a mixture like plant extracts. This study introduced chromatographic methods to identify active natural products without isolating them from their mixtures. In this study, various plant extracts of differing polarities (EtOH, 50% EtOH, and HOH) from species growing in the Lubelskie region of Poland were evaluated for their ability to inhibit tyrosinase. The most active extract identified through spectrophotometric assays was a 50% EtOH extract from Matricaria recutita L. (Chamomilla recutita (L.) Rauschert). Subsequent HPLC-MS analysis allowed for the identification of several active compounds from different classes, including organic acids, glycosylated phenolics, and phenolic acids that interacted with the enzyme. The bioactivity of individual components was confirmed through classical spectrophotometric assays, highlighting ferulic acid (IC50 = 0.484 µM), quinic acid (IC50 = 22.90 µM), and citric acid (IC50 = 24.18 µM) as three representatives of different classes of molecules with inhibitory potential. Furthermore, the whitening capacity of the chamomile extract was investigated in a zebrafish model, demonstrating effective pigmentation inhibition in Danio rerio larvae and validating the proposed chromatographic approach.